RE-EVALUATING USER MOTIVATION IN USING ARCHITECTURAL SOFTWARE IN EACH DESIGN PHASE IN INDONESIA - Horlanso, Valeryn; Susanto, Angeline; Kusuma, Hanson Endra (Jurnal Arsitektur ARCADE, 2022)
Abstract: Digitalized era has caused design software to develop so rapidly. As a result, architects and designers are offered various choices of design software to choose from, and sometimes designers use different software on different design phases. However, the motivation of choosing a specific software in specific phases is still unknown. Therefore, this paper aims to investigate the frequencies of certain architectural software usage in different design phases, along with the user's motivation in choosing the software. Qualitative method with grounded theory approach are used in the study. Data is then analysed with directed content analysis extracted from software external and internal quality in ISO/IEC 25010:2011. The result of this study reveals that in earlier (exploratory) design phases, media with high efficiency (such as SketchUp) are preferred, and later phases show a significant increase in the need for precision. Efficiency and output suitability are highly valued in architectural visualisation and presentation needs.Abstrak: Era digitalisasi telah menyebabkan software desain berkembang sangat pesat. Akibatnya, arsitek dan desainer disuguhkan dengan berbagai pilihan software desain dan seringkali desainer menggunakan software yang berbeda pada setiap fase desain. Namun, alasan memilih software tertentu dalam fase tertentu masih belum jelas diketahui. Oleh karena itu, makalah ini bertujuan untuk meneliti frekuensi penggunaan software arsitektur dalam fase desain yang berbeda, sekaligus alasan pengguna dalam memilih software tersebut. Penelitian ini menggunakan metode kualitatif dengan pendekatan grounded theory. Data yang didapat dianalisis dengan directed content analysis dari ISO/IEC 25010:2011. Hasil penelitian ini mengungkapkan bahwa pada fase desain awal (eksplorasi), media dengan efisiensi tinggi lebih disukai. Sedangkan fase akhir menunjukkan peningkatan yang signifikan terhadap kebutuhan kepresisian. Efisiensi dan kesesuaian outputjuga sangat dicari dalam fase visualisasi dan presentasi arsitektur.